LEGISLATIVE CHARACTERISTICS OF PERMITS IN THE FIELD OF GENERAL SECONDARY EDUCATION FROM THE POINT OF VIEW OF THEIR IMPROVEMENT - Zhukova, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to identify and substantiate the specifics of permits in the field of general secondary education, and to identify ways to improve the procedure for obtaining them. Research methods: general theoretical and analytical methods in combination with systemic and integrated approaches were used. Results: attention is paid to the issue of identification of permits in the field of general secondary education with administrative jurisdiction and administration as a process of their acceptance. It was established that the terminological construction «legality of educational activity within general secondary education is subject to a more detailed disclosure in the following format: «criterion of legality of educational activity, which is ensured in the process of issuing a permit to an institution of general secondary education to conduct the latter activity by an authorized state body, which is the presence in institution undergoing accreditation, founding documents, information on the teaching and scientific-pedagogical staff, as well as data, which certify and confirm the planned professional development of the relevant employees». The article emphasizes the need to define the term «permits in the field of general secondary education» in the field of legal-administrative plane by searching for mechanisms by which legislative prescriptions will be implemented, such as: control and supervision, monitoring, remote (directive) management of institutions of general secondary education, etc. The conclusion was formed that the procedure for granting permits in the field of general secondary education in Ukraine is conceptualized with the help of normative and legal regulation. At the same time, it is well-founded that a review of exclusively legislative approaches to the strategic regulation of processes of licensing and accreditation of institutions of general secondary education and educational programs developed by a scientific and pedagogical team on the basis of the latter will not allow to draw up a complete picture of hypothetical and requested changes in licensing activities in the specified field. These conclusions are important for the development of ways to improve the legislative characteristics of permits in the field of general secondary education through the lens of relevant legislative acts. Discussion: theoretical and methodological basis for studying the procedure for obtaining permits in the field of general secondary education.